2021
DOI: 10.1590/s1678-3921.pab2021.v56.02000
|View full text |Cite
|
Sign up to set email alerts
|

Botanical insecticide formulation with neem oil and D-limonene for coffee borer control

Abstract: The objective of this work was to evaluate the insecticidal activity of a botanical formulation with neem (Azadirachta indica) oil and D-limonene for the control of Hypothenemus hampei, as well as to determine the fatty acid composition of neem oil. Ninety-five percent neem oil was extracted from cold-pressed A. indica seeds, and D-limonene, from citrus peel. Humic extract (organic carbon), potassium, calcium, magnesium, and sulfur were included as additives. The analysis of neem oil by gas chromatography coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…From these 17 studies, 133 comparisons for mortality rate of CBB from 14 different plant families were represented. The plant families that have botanical pesticide potential included in this study were Anacardiaceae (Santos et al, 2013), Apocynaceae (Zorzetti et al, 2012), Arecaceae (Indriati & Samsudin, 2018;Indriati et al, 2021), Euphorbiaceae (Celestino et al, 2016), Fabaceae (Zorzetti et al, 2012), Hypercaceae (Soares et al, 2022), Lamiaceae (Mawussi et al, 2009;Mendesil et al, 2011;Santos et al, 2022), Meliaceae (Zorzetti et al, 2012), Moringaceae (Zorzetti et al, 2012), Myrtaceae (Reyes et al, 2019), Piperaceae (Santos et al, 2010;Santos et al, 2011;Soares et al, 2022), Poaceae (Soares et al, 2022), Rutaceae (Brito et al, 2021), and Urticaceae (Soares et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…From these 17 studies, 133 comparisons for mortality rate of CBB from 14 different plant families were represented. The plant families that have botanical pesticide potential included in this study were Anacardiaceae (Santos et al, 2013), Apocynaceae (Zorzetti et al, 2012), Arecaceae (Indriati & Samsudin, 2018;Indriati et al, 2021), Euphorbiaceae (Celestino et al, 2016), Fabaceae (Zorzetti et al, 2012), Hypercaceae (Soares et al, 2022), Lamiaceae (Mawussi et al, 2009;Mendesil et al, 2011;Santos et al, 2022), Meliaceae (Zorzetti et al, 2012), Moringaceae (Zorzetti et al, 2012), Myrtaceae (Reyes et al, 2019), Piperaceae (Santos et al, 2010;Santos et al, 2011;Soares et al, 2022), Poaceae (Soares et al, 2022), Rutaceae (Brito et al, 2021), and Urticaceae (Soares et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The tangerine peel, a by-product of the tangerine agro-industry, is an excellent example of the valorisation of agricultural waste [45,79,80]. Obtaining an essential oil from the peel through extraction with organic solvents and its subsequent removal by distillation provides a product of natural origin that has very low phytotoxicity in potatoes (Solanum tuberosum) (results not shown), which allows one to obtain from it a candidate for a botanical, natural, and environmentally friendly insecticide [35,81].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some natural substances present in fruits and plant tissues have evolved to become repellents for insects and other pests [19,20]. Such is the case with some terpenes, such as d-limonene [34][35][36][37][38]. This monoterpene has demonstrated its biocidal and insecticidal effects against various pests [35,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this essential oil is characterized by the prevalent presence of the D-limonene molecule, whose toxicity against insects has been studied for other species, such as the coffee berry borer Hypothenemus hampei (Ferrari, 1867) (Coleoptera: Curculionidae)(Brito et al 2021). Our results have showed that neem oil effectively prevents the development of this pest.…”
mentioning
confidence: 99%